PEMBERDAYAAN MASYARAKAT LOKAL DALAM PRESPEKTIF KEBIJAKAN PEMERINTAH DAERAH DI KAMPUNG IVIMAHAD DI DISTRIK KURIK KABUPATEN MERAUKE - Syahruddin uddin (SOCIETAS, 2016)
Study is to analyze the empowerment of local communities as a form of poverty and unemployment, to describe and analyze the regional government policy to increase the independence and well-being of local communities, analyzing the factors that hinder and support the empowerment of local communities against government policy Regions.Metode research used in this research is qualitative research. Research conducted through observation, literature, data collection and interviews, quantitative methods for empowering local communities.The results showed that Ivimahad village government should increase the strength and weaknesses of the community, or to the community in the form semberdaya preparation, opportunity, knowledge, and expertise in order to increase the capacity of the community themselves. Implementation of government functions of the village said to be successful if the people in the village have bardaya Ivimahat aspect of education, economy. Social and cultural as well as an adequate infrastructure, it certainly can reduce the levels of poverty and unemployment.